Prolactin receptor (PRLR) gene polymorphism in Chios, White Karaman and Awassi sheep breeds - Ozmen, Ozge; Seker, Ibrahim; Ertugrul, Okan; Ozkan, Emel; Tekin, Nilgun (Archiv Fur Tierzucht, 2011)
The objective of the present study was to determine the polymorphism in the prolactine receptor (PRLR) gene in Chios, White Karaman and Awassi, which are native sheep breeds in Turkey. By means of PRLR gene sequence homology between sheep and humans, two primer pairs were designed for polymerase chain reaction (PCR) amplification within intron 1 and exon 10 of the PRLR gene in sheep. A total of 160 amplicons (99 for intron 1 and 61 for exon 10) were subjected to DNA sequence analysis. For intron 1, 6 different haplotypes were determined. For exon 10, 7 different haplotypes were obtained. Some variations determined for exon 10 (g.14A>T p.Q14L; g.160G>A p.D160N; g.166G>A p.E166K; g.167A>T p.E167V; g.176A>T p.H176L; g.206G>A p.S206N; g.208G>A p.G208R) led to changes in the amino acids, but no amino acid changes were determined in g.2A>T, g.81A>G, g.138A>G, g.186C>T, g..207T>C. It was noted in particular that White Karaman and Awassi were similar to each other in both PRLR exon 10 and intron 1 haplotypes, whereas the Chios breed had a different variation.
Keywords: Turkish sheep breeds; prolactin receptor gene; polymorphism